Energy efficiency of electromechatronic systems with planetary gears - Nasima A. Maksudova (PROBLEMS OF ENERGY AND SOURCES SAVING, 2025)
Relevance: improving the energy efficiency of equipment and production processes in all countries of the world has become one of the priority areas of economic development. In modern industry, up to 60% of the consumed electricity comes from mechatronic electric drive systems, which makes it relevant to analyze the possibilities of increasing their energy efficiency. Aim: analysis of the parameters of energy efficiency and efficiency of mechanical planetary gears used in electric drive modules of mechatronic systems to improve them. Methods: the theory of electric drive mechatronic systems with planetary gears and comparative analysis methods are used; calculations of the efficiency of planetary gears as part of electromechatronic systems are analyzed. Results: the use of planetary gears in electromechatronic modules to improve energy efficiency is preferable compared to other types of gears.